Supramolecular Luminescence from Oligofluorenol-Based Supramolecular Polymer Semiconductors: Experimental Investigation - Guang-Wei Zhang; Long Wang; Ling-Hai Xie; Jin-Yi Lin; Wei Huang (New Innovations in Chemistry and Biochemistry Vol. 1, 2021)
Supramolecular luminescence stems from non-covalent exciton behaviors of active \(π\)-segments in supramolecular entities or aggregates via intermolecular forces. Herein, a \(π\)-conjugated oligofluorenol, containing self-complementary double hydrogen bonds, was synthesized using Suzuki coupling as a supramolecular semiconductor. Terfluorenol-based random supramolecular polymers were confirmed via concentration-dependent nuclear magnetic resonance (NMR) and dynamic light scattering (DLS). The photoluminescence spectra of the TFOH-1 solution exhibit a green emission band (g-band) at approximately 520 nm with reversible features, as confirmed through titration experiments. Supramolecular luminescence of TFOH-1 thin films serves as robust evidence for the aggregates of g-band. Our results suggest that the presence of polyfluorene ketone defects is a sufficient condition, rather than a sufficient-necessary condition for the g-band. Our results also show that non-covalent network precursors in the ink are crucial to the thin-film optoelectronic behaviors and phase morphologies. Supramolecular electroluminescence will push organic devices into the fields of supramolecular optoelectronics, spintronics, and mechatronics.